The interdependence of the regional environment state with the level of enterprise development = Współzależność stanu otoczenia regionalnego z poziomem rozwoju przedsiębiorstw - Malinowski, Mariusz (Zielona Góra: Faculty of Economics and Management Press)
The purpose of this article is to determine to what extent the state of the regional environment, influences the development of companies located in different regions. In the first part, the paper characterizes the regional environment and presents it as a factor in the development of enterprises. In the second part, based on statistical data, the relationship between the development of regional environment and the enterprise development in individual voivodeships in 2006-2010 was examined.
Keywords: otoczenie przedsiębiorstwa; otoczenie regionalne; rozwój przedsiębiorstw; enterprise environment; regional environment; development of enterprises